Mixed reality in an operating room using hololens 2—The use of the remote assistance from manufacturers techinicians during the surgeries - Veloso, Rita (2021)
The aim of this work is that the participants, using HoloLens 2 and Dynamics 365 Remote Assistance, can receive all the training and information necessary for the correct application of prosthesis and medical devices remotely, from a support center of the manufacturers, avoiding the displacement and presence of these technicians during surgeries. After implementing this method, an analysis will be made on its impact, avoiding displacement and the presence of technicians during surgery, in terms of increasing satisfaction and improving the experience of the participants, reduction of various risks (including the risk of infection) and on reduction of some economic and environmental costs.